Interreligious Peacebuilding and Minority Problems in Islamic Mystical Teachings - Mottaghi, Hossein (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Differences are a necessity that humans cannot deny, including differences in matters of belief and religion. Humans living side by side in a community should be able to create a harmonious, safe and peaceful life. However, harmonious relations between religious adherents are often disrupted for various reasons. Religious people, who should respect and care for one another, are often provoked so that differences, which should be understood as a necessity and a gift, sometimes fuel divisions. By using Library Studies, this study explores sources that can be used as arguments for religious people to respect each other and create peace, especially in Islamic mystical teachings. It can be concluded that peace and harmony are the hope of everyone, including those living in a country. Differences should not be used as an excuse to criticize each other and eradicate the existence of different groups; this research found that people must complement each other and realize the importance of maintaining unity, maintaining relationships in interacting and living together among religious communities.